Providing a model of consumer behavior in creating brand attachment with an emphasis on the packaging component of food industry companies - maziar Ghasemzadeh Sangroudi; karim hamdi; SHADAN VAHABZADEH MUNSHI (ارزش آفرینی در مدیریت کسب و کار)
Abstract The current research was conducted with the aim of providing a model of consumer behavior in creating brand attachment, emphasizing the packaging component of food industry companies. It is considered a qualitative-quantitative (mixed) research method. The sample of the qualitative section with 12 interviews with marketing, academic and food industry experts, and the quantitative section with the Cochran formula of limited societies included 384 managers and senior experts of Tehran food industry companies. In the first step of the research, the coding of specialized research interviews was performed using thematic qualitative analysis with MAXQDA 20 software and fuzzy Delphi method with MatLab software, structural-interpretive analysis with MicMac software; in the next step, the results of confirmatory factor analysis with Smart PLS 3.0 software. Based on the results of qualitative analysis, three comprehensive categories including packaging, brand attachment and consumer behavior were identified as the main components. Based on the influence-dependence diagram, the structures of communication factors, logistic factors, economic factors, bio-social factors have high influence power and are under little influence, and are placed in the area of independent structures. The constructs of brand loyalty, brand awareness, perceived quality, and brand associations also have high dependence but little influence, so they are considered dependent constructs. The results of the quantitative part, while confirming the research hypotheses, showed that the proposed model has good validity. Extended Abstract Introduction According to the opinions and findings of recent researches, it is clear that the packaging characteristics might have a major contribution in creating brand attachment, but this problem should be done with a careful and precise examination of the consumer's behavior, because only by this way can correct decisions be made regarding the packaging component. Therefore, this study aims to help brand managers who are trying to improve brand performance in order to create attachment to their product and collection. In addition, this research can be an effective step in the field of improving brand management with an emphasis on creating effective value in the field of packaging. According to the above, the main innovation of this research may be considered in entering the field of brand attachment through packaging, and providing a completely native model suitable for the domestic business environment. Finally, in this research, we are looking for an answer to this question: What dimensions and components form the consumer behavior model in creating brand attachment with an emphasis on the packaging component of food industry companies? Theoretical framework Literature A person's behavior is how he acts or behaves in a certain situation. Each person has different views, opinions, desires, tastes and needs; hence, consumer behavior deals with the way consumers spend their income on various goods and services. For example, if a consumer has $2,000 and has different options such as movies, clothes, and food to spend the money on, there are different ways to spend the money. He may spend the entire amount on one option, or divide it between two or more options. The way a consumer uses his money shows his consumer behavior (Khan, Sheikh, Ashraf & Yu, 2022). Taylor et al (2023) conducted a study titled the effect of packaging on brand association in tobacco products. This research was carried out as a survey among a sample consisting of teenagers (2469 people) and adults (12046 people) in the UK. Based on the results obtained, it was found that the use of attractive packaging has a positive effect on brand associations and brand loyalty. Romeo-Arroyo, Jensen, Hunneman & Velasco (2023) conducted a study titled evaluating the effect of symmetry, curvature and packaging mark on the perception of brand superiority. In this survey study, the effect of different dimensions of packaging including curvature, symmetry, and marking was measured on consumers' perception of superiority in four different categories of food products (chocolate, coffee, jam, and ice cream). Overall, a significant positive effect of symmetry, and a significant effect of brand on brand superiority perception were identified. It seems that the effect of sign and curvature on consumers' perception of superiority is more influenced by the texture and classification of the product. Research background Taylor et al (2023) conducted a study titled the effect of packaging on brand association in tobacco products. This research was carried out as a survey among a sample consisting of teenagers (2469 people) and adults (12046 people) in the UK. Based on the results obtained, it was found that the use of attractive packaging has a positive effect on brand associations and brand loyalty. Romeo-Arroyo, Jensen, Hunneman & Velasco (2023) conducted a study titled evaluating the effect of symmetry, curvature and packaging mark on the perception of brand superiority. In this survey study, the effect of different dimensions of packaging including curvature, symmetry, and marking was measured on consumers' perception of superiority in four different categories of food products (chocolate, coffee, jam, and ice cream). Overall, a significant positive effect of symmetry, and a significant effect of brand on brand superiority perception were identified. It seems that the effect of sign and curvature on consumers' perception of superiority is more influenced by the texture and classification of the product. Tabatabai Yeganeh (2021) conducted a study titled investigating the effects of brand experience, brand image and brand trust on brand attachment and purchase intention. The findings of the research showed that brand image has a direct and significant effect on customers' purchase intention and customer trust. Also, brand experience has shown a significant direct effect on brand image, brand trust, and customers' dependence on the brand. Finally, the trust of the brand leads to the increase of the customers' dependence on the brand, and the customers' dependence on the brand also increases the motivation of the customers to buy. Research methodology The purpose of this research is in the field of developmental-applicable research. The statistical sample in the qualitative stage included 12 experts and university professors in the fields of marketing management, experts in the field of food industry companies, and consumer behavior. The sample volume is determined based on reaching theoretical saturation. According to the topic and objectives of the research, the semi-structured interview method has been used to collect data. In the quantitative phase of the research, the statistical population in this phase of the research includes 300 food industry companies, which includes an unlimited number of food industry companies' customers. Using Cochran's formula for unlimited communities, the required number of 384 people was calculated and the final samples were selected through random-cluster sampling with proportional distribution. To ensure obtaining sufficient data, 400 questionnaires were distributed, of which 393 complete questionnaires were returned. In order to determine the validity and reliability of the interviews, two methods of re-testing and double-coder agreement were used. In this research, thematic analysis method was used to analyze qualitative data. In the next step, the results of confirmatory factor analysis are presented. Then the existing categories are leveled with the structural-interpretive method and the initial research model is designed. Finally, partial least squares method has been used to validate the model. Qualitative analysis was performed with MAXQDA 20 software, structural-interpretive analysis with MicMac software and partial least squares method with Smart PLS 3.0 software. Research findings In order to evaluate the validity and reliability of the interviews, two methods of coder agreement and retest reliability were used. As shown in Table 3, the coefficients obtained in both methods were higher than the threshold of 0.6; therefore, the reliability and validity of the interviews are confirmed. Qualitative content analysis was done with thematic analysis approach in six consecutive steps. The present research has identified 42 subcategories by examining and categorizing the descriptive codes obtained from the interview texts which, according to their semantic similarity and affinity, in the main concepts were identified as follows: packaging (communication factors, logistic factors, economic factors, environmental factors and social responsibility), brand attachment (brand loyalty, brand awareness, perceived quality and brand associations), consumer behavior (personal, cultural, psychological (motivational) and marketing mix). The results of the quantitative part of the research showed that the proposed model has good fit and validity. Conclusion Based on the results of qualitative analysis, three main dimensions including packaging, brand attachment and consumer behavior were identified. And based on the components detected in relation to these three dimensions, the structures of the primary model of consumer behavior in creating brand attachment were identified as follows: communication factors, logistics factors, economic factors, bio-social factors, brand loyalty, brand awareness, perceived quality, brand associations, personal, cultural, psychological, marketing mix. In relation to the test of the first and second hypotheses, which indicates the effectiveness of the marketing mix, the following suggestions are presented: reducing the price of products, using online distribution channels (such as a contract with Snap Food, etc.), improving product quality by using high-quality raw materials. These findings are consistent with the results of Rojas-Méndez & Khoshnevis (2023), Vila-Lopez & Küster-Boluda (2021), Chen (2021), Moodie, et.al. (2022), Chakraborty & Dash (2023), Chan & Chiu (2022), Vila-Lopez & Küster-Boluda (2021), Cleff, Lin & Walters (2021), Hwang, Choe, Kim & Kim (2021), Fathi, Torabi & Shayghi Azarzad (2021), Gómez-Suárez & Veloso (2020), Nguyen, Parker, Brennan & Lockrey (2020), Gefen & Straub (2014), Amini & Kaidi (2014), Das, Agarwal, Malhotra & Varshneya (2019), Shukla, Misra & Singh (2023), Moody, et al. (2022), Shetty & Fitzsimmons (2022), Tabatabai Yeganeh (2021), Chan & Chiu (2022), Hwang, Choe, Kim & Kim (2021), Ho & Chung (2020), and Gómez-Suárez & Veloso (2020). In relation to the results obtained from the third to fifth hypotheses regarding the impact of psychological factors, the following suggestions are presented: the use of merry and attractive visual elements to attract young customers; using attractive and challenging billboard ads to attract customers' attention; using sensory marketing techniques. In relation to the results obtained from the analysis of the sixth to ninth hypotheses regarding personal factors, the following suggestions are presented: customer segmentation, using CRM software to improve customer relations, conducting surveys among customers, personalizing products for different customer groups. In relation to the result obtained from the analysis of the tenth hypothesis in relation to social factors, the following suggestions are presented: creating a customer club, creating pages in the space of social networks to increase interaction with customers, inserting a slogan related to social responsibility on the packaging In relation to the result obtained from the analysis of the eleventh and twelfth hypotheses in relation to communication factors, the following suggestions are presented: the use of attractive colors in product packaging; providing detailed information regarding the ingredients used in the product's manufacture; using the appropriate logo on the packaging. In relation to the result obtained from the analysis of the thirteenth hypothesis in relation to economic factors, the following suggestions are presented: cooperation with domestic companies to reduce the total cost of packaging, designing packaging according to the size of the product, using social media for marketing. In relation to the result obtained from the analysis of the fourteenth hypothesis in relation to logistics factors, the following suggestions are presented: use of three-layer packaging to increase product durability, use of materials that prevent product spoilage. In relation to the results obtained from the analysis of the fifteenth and sixteenth hypotheses regarding cultural factors, the following suggestions are presented: the use of elements of Iranian culture in advertising, focusing on the use of nostalgic elements in the introduction and advertising of products (due to the strong sense of nostalgia among people of Iran).